Smoking Prevalence and Associated Factors as well as Attitudes and Perceptions towards Tobacco Control in Northeast China - Li, Zhijun (Int J Environ Res Public Health, 2015)
Objectives: The present study aimed to investigate the prevalence of smoking and environmental tobacco smoke (ETS), the associated factors of current smoking among adults, and their attitudes and perceptions towards tobacco control. Methods: A population-based cross-sectional survey was conducted in 2012 using a self-reported questionnaire. A representative sample of adults aged 18–79 years was collected in the Jilin Province of Northeast China by a multistage stratified random cluster sampling design. Descriptive data analysis was conducted, and 95% confidence intervals (CI) of prevalence/frequency were calculated to enable comparisons between the alleged differences and similarities. Multivariable logistic regressions were used to examine the risk factors associated with current smoking. Results: 21,435 adults responded to the survey (response rate: 84.9%). The overall prevalence of ever smoking, current smoking, and former smoking or smoking cessation was 39.1% (95% CI: 38.3–39.9), 31.8% (95% CI 31.1–32.6), and 7.3% (95% CI: 6.9–7.7), respectively. The proportion of ETS exposure among adult non-smokers in Jilin Province was 61.1% (95% CI: 60.1–62.1), and 23.1% (95% CI: 22.3–24.0) of the non-smokers reported daily ETS exposure. The proportion of ETS exposure at home was 33.4% (95% CI: 32.5–34.4), but the proportion of ETS exposure at restaurants was lower (6.5%) (95% CI: 6.0–7.1). More than 90% of the participants had positive attitudes and perceptions towards tobacco control, but 23.2% (95% CI: 22.5–24.0) of them did not agree with the perception of “smoking is fully quit in public places”, and almost half of the adults (49.5%) (95% CI: 48.7–50.3) did not agree with the perception of “hazards of low-tar cigarettes are equal to general cigarettes”. Conclusions: Smoking and exposure to ETS are prevalent among adults from the Jilin Province of Northeast China. Our findings suggest that tobacco control should be advocated in Northeast China. Anti-smoking campaigns and legislation should be built into the public health curriculum and government policy.